2022
DOI: 10.1051/0004-6361/202243746
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical essence of the eccentric von Zeipel-Lidov-Kozai effect in restricted hierarchical planetary systems

Abstract: Aims. The eccentric von Zeipel–Lidov–Kozai (ZLK) effect is widely used to explain dynamical phenomena in a variety of astrophysical systems. The purpose of this work is to clarify the dynamical essence of the eccentric ZLK effect by constructing an inherent connection between this effect and the dynamics of secular resonance in restricted hierarchical planetary systems. Methods. Dynamical structures of apsidal resonance were studied analytically by means of perturbative treatments. The resonant model was formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, there exists a third type, in which orbit flips happen with initial intermediate eccentricities. Sidorenko (2018) and Lei & Gong (2022b) demonstrated that the ELK effect is essentially a secular resonance and the flipping orbits are resonant trajectories with the resonant center located at i = 90°.…”
Section: = -mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there exists a third type, in which orbit flips happen with initial intermediate eccentricities. Sidorenko (2018) and Lei & Gong (2022b) demonstrated that the ELK effect is essentially a secular resonance and the flipping orbits are resonant trajectories with the resonant center located at i = 90°.…”
Section: = -mentioning
confidence: 99%
“…The related mechanism is referred as the ELK effect Naoz 2016). Recent research has demonstrated that the ELK effect is essentially a secular resonance with the critical argument j sign z v w = W + ( ) , i.e., the longitude of pericenter for prograde or retrograde orbits, which librates around 0 or π on a very long timescale (Sidorenko 2018; Lei 2022a; Lei & Gong 2022b). In this section, we are going to reveal a new orbit-flip mechanism by the combined ELK and stellar oblateness (J 2 ) effects.…”
Section: A New Type Of Orbit Flip With the Elk-j 2 Effectmentioning
confidence: 99%